American law and legal systems - Calvi, James V., Coleman, Susan (prentice-hall international, 2000)
American Law and Legal Systems examines the philosophy of law within a political, social, and economic framework with great clarity and insight. Readers are introduced to operative legal concepts, everyday law practices, substantive procedures, and the intricacies of the American legal system. Eliminating confusing legalese, the authors skillfully explain the basics, from how a lawsuit is filed to the final appeal. This new edition provides essential updates to forensic and scientific evidence, contract law, family law, and includes new text boxes and tables to help students understand, remember, and apply central concepts.